Anion exchange resin as support for invertase immobilization - R.R. Ribeiro; M. Vitolo (São Paulo State University (UNESP), 2005)
The invertase (EC 3.2.1.26) from Saccharomyces cerevisiae was employed as a model enzyme in the evaluation of the adsorption capacity of DOWEX-1X8-50®, a basic anion exchange resin, when used as support in enzyme immobilization. By mixing 100mg of resin with 27mg of invertase (pI = 4.0) in buffer solution (pH 4.6, 25°C), stirred at 100rpm, an adsorption of 93% was achieved. The activities (1U = amount of enzyme forming 1mg reducing sugars/min) of soluble and insoluble invertase were 0.084 U/mgE and 0.075 U/mgE, respectively, giving an immobilization coefficient of 90.4%. The immobilized invertase had a higher thermal stability than the soluble form. The highest activity was observed at pH 4.5 in both forms of the enzyme, whereas the pH stability ranges for soluble and insoluble invertase were 3.5-5.0 and 4.5-5.5, respectively. The kinetic constants for soluble invertase were K M = 18.3 mM and Vmax = 0.084 U/mgE, and for the insoluble form, KM = 29.1 mM and Vmax = 0.075 U/mgE. The resin tested adsorbed the invertase very well, provided the enzyme molecule had a net negative charge, i.e., the immobilization and reaction procedures had to be carried out at pH > pI.